Microcomposite ceramics modeling - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (1999, 1999)
Computer modeling of microcomposite ceramic grain structure was carried out taking into account the correlative fields of C-particles, and the principles of high packing and self-similarity. The behavior of the spirally organized microcomposite ceramic structure model is in accordance with studies of polytypes, nano- and other mesoscopic particles. It was shown that in grains there is microplasticity within the 2D electron lattice due to the high mobility of self-organised mesoscopic particle blocks. Therefore a high level of size quantization and microplasticity intergrain structure is reached under low temperatures.